2009
DOI: 10.1021/np900460j
|View full text |Cite
|
Sign up to set email alerts
|

Biphenyls from Berberis koreana

Abstract: Three new biphenyls, berbekorin A (1), 2'-hydroxy-3,4,5-trimethoxybiphenyl (2), and 4,5-dihydroxy-3-methoxybiphenyl (3), together with 11 known biphenyls (4-14), were isolated from the n-hexane-soluble fraction of the MeOH extract of the trunk of Berberis koreana. The structures of 1-3 were determined by spectroscopic methods, including 1D and 2D NMR analysis. Compound 1 exhibited cytotoxic activity against the SK-MEL-2 skin melanoma cell line, in particular. Moreover, compounds 2, 5, 6, and 14 inhibited NO pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 25 publications
2
22
1
Order By: Relevance
“…[1][2][3] As part of our efforts to screen the bioactive constituents of Korean medicinal plants with potential anti-tumor activities, we found that an MeOH extract of the trunk of Berberis koreana exhibited considerable cytotoxic activity against cultured human tumor cell lines in vitro. 4,5) B. koreana (Berberidaceae), one of the endemic Korean plants, is used as a traditional Korean medicine for treating fever, gastroenteritis, sore throats, and conjunctivitis. 6) Previous phytochemical investigations have isolated such alkaloids as benzylisoquinoline and protoberberine derivatives from this plant.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] As part of our efforts to screen the bioactive constituents of Korean medicinal plants with potential anti-tumor activities, we found that an MeOH extract of the trunk of Berberis koreana exhibited considerable cytotoxic activity against cultured human tumor cell lines in vitro. 4,5) B. koreana (Berberidaceae), one of the endemic Korean plants, is used as a traditional Korean medicine for treating fever, gastroenteritis, sore throats, and conjunctivitis. 6) Previous phytochemical investigations have isolated such alkaloids as benzylisoquinoline and protoberberine derivatives from this plant.…”
mentioning
confidence: 99%
“…[7][8][9] Our earlier phytochemical investigation of B. koreana by bioassay-guided purification resulted in the isolation of biphenyls and triterpenoids with cytotoxicity. 4,5) Our continuing search for active constituents from the n-hexane soluble fraction led to the isolation of three steroids, including the new 3-O-fatty acid ester of a steroid, itesmol 3-Opalmitate (1) (Fig. 1A).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Pyrinae is the only taxon that produces biphenyls and dibenzofurans as pathogen-induced antimicrobial phytoalexins (Kokubun and Harborne, 1995). Some other plant families, such as Fabaceae, Alliaceae, and Berberidaceae, contain related compounds as preformed secondary metabolites (Khan and Shoeb, 1984;Carotenuto et al, 1998;Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Berberis koreana belonging to a family of Berberidaceae has been used as a medicinal plant for the treatment of fever, conjunctivitis, sour throat, diarrhoea, parasite infections, and trachoma infections 6–8. In recent years, Berberis spp., including B. aristata , B. vulgaris , B. asiatica , B. chitria , B. lyceum , B. heterophylla and B. aetnensis , have been well investigated for their potential health benefits such as antimicrobial, anti‐inflammatory, and anti‐cancer properties 8–17. The compounds leading to pharmacological activities of Berberis spp.…”
Section: Introductionmentioning
confidence: 99%